Genome-Wide Association Study of Autistic-Like Traits in a General Population Study of Young Adults - Jones, Rachel M.; Cadby, Gemma; Melton, Phillip; Abraham, Lawrence; Whitehouse, Andrew; Moses, Eric (Frontiers in Human Neuroscience, 2013)
Research has proposed that autistic-like traits in the general population lie on a continuum, with clinical Autism Spectrum Disorder (ASD) representing the extreme end of this distribution. Inherent in this proposal is that biological mechanisms associated with clinical ASD may also underpin variation in autistic-like traits within the general population. A genome-wide association study using 2,462,046 single nucleotide polymorphisms (SNPs) was undertaken for ASD in 965 individuals from the Western Australian Pregnancy Cohort (Raine) Study. No SNP associations reached genome-wide significance (p < 5.0 x 10-8). However, investigations into nominal observed SNP associations (p < 1.0 x 10-5) add support to two positional candidate genes previously implicated in ASD aetiology, PRKCB1 and CBLN1. The rs198198 SNP (p = 9.587 x 10-6), is located within an intron of the protein kinase C, beta 1 (PRKCB1) gene on chromosome 16p11. The PRKCB1 gene has been previously reported in linkage and association studies for ASD, and its mRNA expression has been shown to be significantly down regulated in ASD cases compared with controls. The rs16946931 SNP (p = 1.78 x 10-6) is located in a region flanking the Cerebellin 1 (CBLN1) gene on chromosome 16q12.1. The CBLN1 gene is involved with synaptogenesis and is part of a gene family previously implicated in ASD. This GWA study is only the second to examine SNPs associated with autistic-like traits in the general population, and provides evidence to support roles for the PRKCB1 and CBLN1 genes in risk of clinical ASD.